2021
DOI: 10.3390/nu13041165
|View full text |Cite
|
Sign up to set email alerts
|

Functional Food and Bioactive Compounds on the Modulation of the Functionality of HDL-C: A Narrative Review

Abstract: Cardiovascular diseases (CVD) remain a serious public health problem and are the primary cause of death worldwide. High-density lipoprotein cholesterol (HDL-C) has been identified as one of the most important molecules in the prevention of CVD due to its multiple anti-inflammatories, anti-atherogenic, and antioxidant properties. Currently, it has been observed that maintaining healthy levels of HDL-C does not seem to be sufficient if the functionality of this particle is not adequate. Modifications in the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 123 publications
1
12
0
Order By: Relevance
“…As a special subclass of flavonoids, quercetin is a natural bioactive compound abundantly present in common cereal grains, especially in buckwheat [ 64 ], followed by rice [ 50 ], quinoa [ 42 ], corn [ 43 ] and oat [ 39 ]. Quercetin has displayed notable antioxidative and anti-inflammatory effects and shows potential benefits for muscle function [ 65 ]. By increasing the expression of adiponectin, quercetin stimulates muscle-fiber-type transformation from fast-twitch to slow-twitch myofibers [ 66 ].…”
Section: Whole Grain Bioactive Compounds In the Regulation Of Skeleta...mentioning
confidence: 99%
“…As a special subclass of flavonoids, quercetin is a natural bioactive compound abundantly present in common cereal grains, especially in buckwheat [ 64 ], followed by rice [ 50 ], quinoa [ 42 ], corn [ 43 ] and oat [ 39 ]. Quercetin has displayed notable antioxidative and anti-inflammatory effects and shows potential benefits for muscle function [ 65 ]. By increasing the expression of adiponectin, quercetin stimulates muscle-fiber-type transformation from fast-twitch to slow-twitch myofibers [ 66 ].…”
Section: Whole Grain Bioactive Compounds In the Regulation Of Skeleta...mentioning
confidence: 99%
“…Exercise is associated with higher HDL levels and better HDL performance such as the concentrations and functionality, however diets have a two-sided effect, meaning that different dietary patterns may have distinct beneficial or detrimental effects on HDL effectiveness [9]. According to some studies on the relationship between food and HDL, it suggested that a nutritious diet, which mostly consisted of fruits, vegetables, legumes, fish, nuts, and olive oil, could boost the amount of HDL cholesterol particles in the blood [9]. Based on ACC/AHA 2019 guidelines for a healthy dietary pattern to prevent CVD, they recommend that decreasing the daily intake of saturated fatty acids (SFA), processed meats and sodium; and limit the consumption of high-sugar beverages and trans fats [9].…”
Section: Diet Recommendationmentioning
confidence: 99%
“…According to some studies on the relationship between food and HDL, it suggested that a nutritious diet, which mostly consisted of fruits, vegetables, legumes, fish, nuts, and olive oil, could boost the amount of HDL cholesterol particles in the blood [9]. Based on ACC/AHA 2019 guidelines for a healthy dietary pattern to prevent CVD, they recommend that decreasing the daily intake of saturated fatty acids (SFA), processed meats and sodium; and limit the consumption of high-sugar beverages and trans fats [9]. Additionally, the plant-based dietary pattern, such as the Mediterranean diet (MD), has been considered one of the healthy diet ways to prevent CVD because traditional MD has consisted of low saturated fat, and trans-fat and is rich in complex carbohydrates and fibre [10].…”
Section: Diet Recommendationmentioning
confidence: 99%
See 2 more Smart Citations